PERLINDUNGAN HUKUM KONSUMEN ATAS PERJANJIAN PENERBITAN KARTU KREDIT (STUDI MARKETING PT.BCA,TBK.BRASTAGI SUPERMARKET MEDAN) - Gulo, Syukur Imanjaya; Siahaan, Abbray Nico Tampati; Aisyah, Aisyah (JURNAL MUTIARA HUKUM, 2021)
The issuance of a credit card (credit card / CC) has a promise to make, of course there will be an agreement for the parties making it. Legal issues in the case of the agreement to issue the CC, are then submitted to the card holder by the issuer after going through a process of rigorous questions, research and checking of consumer data regarding the identity and assets of the prospective card holder, until the CC issuer is sure that the card user is capable and able. fulfill the obligation to pay bills by the bank as a result of the CC user being made by the card user in a place that accepts the use of the card (merchant). for this means that there arises a relationship between the parties who make it, where the relationship based on the existing bond of the contract is made by the parties which must certainly meet all the requirements in the issuance of the CC. This research is a juridical method with descriptive research type. Research data is secondary data. Consists of: primary legal materials: related laws and regulations, secondary legal materials: books related to research and so on, tertiary legal materials: dictionaries and so on. This study obtained several results, as follows: Customers as consumers have protection in the Republic of Indonesia, there is legal protection provided to consumers who hold CC issuance. The instrument is that the banking sector has given or carried out the stage of offering or introducing banking products, especially CC, the bank tries to provide explanatory information to potential customers or customers. this matter is in the UUTPK rule Article 4 letter c regarding consumer rights, then Article 7 letter c regarding what are the obligations of business actors to provide information to consumers. The transaction stage is the stage when there is an agreement between the customer and the bank through the application signature process, and there is also a form data filling that is made unilaterally by the bank, and approved by the customer, so that there is a legal relationship between the two parties. UUTPK is the law needed by consumers in Indonesian society to protect consumer complaints from business actors who behave unfairly. Consumers must know their rights as consumers.